FAKTOR PENENTU FIRM VALUE PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS DI BEI - Andi Chandra; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The research objectives was aimed at examining the effect of profitability, liquidity, leverage, firm size, and sales growth on firm value in the consumer non-cyclicals sector listed on the IDX for the 2019-2021 period. Secondary data in quantitative form is the data used in this study. The research sample contained in this research was 24 companies. The data testing technique used was the classic assumption test through the IBM SPSS statistic 25. The results of this study indicated that profitability had a positive and significant effect on firm value, liquidity had no effect and positive on firm value, leverage had no effect and positive on firm value, firm size had a negative and significant effect on firm value and sales growth had no effect and negative on firm value.